Evaluasi Sistem Informasi Perpustakaan SMP Negeri 16 Jakarta Menggunakan Metode Pieces - Marsela Nihim; Agus Budiyantara (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the digital era, the use of information technology in schools is essential to support more effective teaching and learning activities. SMP Negeri 16 Jakarta has implemented a digital-based library information system to replace manual methods. This system was evaluated using the PIECES method, covering six main aspects: Performance, Information Quality, Cost Efficiency, Security Control, Resource Efficiency, and Service Quality. The evaluation results showed that each aspect achieved good ratings, with average system performance at 34.6%, information quality at 39.9%, cost efficiency at 32.5%, security control at 37.7%, resource efficiency at 34.6%, and service quality at 33.8%. This evaluation indicates that the library information system at SMP Negeri 16 Jakarta is functioning effectively and efficiently. However, regular evaluations and system enhancements are necessary to ensure that the system continues to meet the library’s and users’ needs in the future.